Effectiveness of Innovation Platforms in Enhancing the Viability of the Wheat Seed Sector in Terbol Station, Lebanon - Saad, Sarah; Dhehibi, Boubaker; El Amil, Rola; Machlab, Hassan; M. Oumer, Ali; Souissi, Asma; Akramov, Kamiljon; Baum, Michael; Belhouchette, Hatem; Darwich, Salem (International Center for Agricultural Research in the Dry Areas, 2023)
The objective of this research was to assess the effectiveness of the innovation platform (IP) (Terbol Station) on the wheat seed sector in Lebanon. Data were collected from 16 seed producers after identifying and mapping the key stakeholders in the seed sector. Descriptive statistics was used to categorize and evaluate the efficacy of the innovation platform by identifying six groups: seed availability and access, knowledge and training, seed production and market impact, incentives, joint planning, and the situation of the seed sector in Lebanon. Incentives and joint planning were found to be the primary groups of the IP that the farmers emphasized their importance. The correlation between different groups was found to be statistically significant. Farmers noted that the wheat seed sector is non-profitable and, therefore, needs financial support and joint planning of the value chain. The study recommends the intervention of the government and the Ministries of Agriculture and Economy & Trade by customizing governance strategies and policies. In addition, the adaptation of regulatory measures of the wheat seed sector and agricultural guidance can provide essential information, recommendations, and expertise to optimize the production, distribution, and utilization of seeds in Lebanon.